The practical guide to HIPAA privacy and security compliance - Herold, Rebecca; Beaver, Kevin (Boca Raton : Auerbach Publications, 2015)
'Updated and revised, with several new sections, this one-stop resource for HIPAA privacy and security provides immediately applicable advice for any organization's unique situation. It defines what HIPAA is, what it requires, and what can be done to achieve and maintain compliance. It describes the HIPAA Privacy and Security Rules and compliance tasks in easy-to-understand language and enables organizations to determine how HIPAA will impact them. Anyone preparing an organization for HIPAA laws will receive expert guidance on requirements and other commonly-discussed topics'--
'Preface Introduction to this Book The Practical Guide to HIPAA Privacy and Security Compliance is designed to help you understand what the Health Insurance Portability and Accountability Act (HIPAA) is about, what it requires, what you can do to work toward compliance, and how you can maintain compliance on an ongoing basis. We have designed this book to be the one stop'how-to' practical reference for real-world HIPAA privacy and security advice that you can immediately apply to your organization's unique and specific situation, based upon the authors' actual experiences helping hundreds of covered entities (CEs) and business associates (BAs) to meet HIPAA compliance. This book describes the HIPAA Privacy and Security Rules and compliance tasks in easy to understand language. Although we provide actual definitions and passages from the regulatory text where appropriate, instead of focusing on technical and legal theory and jargon, we lay out what you actually need to do according to the final HIPAA Privacy and Security Rules, as well as the Health Information Technology for Economic and Clinical Health Act and the changes that came with the 2013 Omnibus Rule, to become compliant. All these HIPAArelated requirements are very complex. Privacy and security are also very complex. Given that, we don't claim to have coverage in this book AU: Is it'--
Includes bibliographical references and index.
Keywords: Medical records -- Law and legislation -- United States; Medical records -- Access control -- United States; Medical care -- Security measures -- United States; Health insurance continuation coverage -- United States